A decrease in physiological arousal accompanied by stable behavioral performance reflects task habituation - Micula, Andreea; Rönnberg, Jerker; Zhang, Yue; Ng, Elaine Hoi Ning (Frontiers in Neuroscience, 2022)
Despite the evidence of a positive relationship between task demands and listening effort, the Framework for Understanding Effortful Listening highlights the important role of arousal on an individual’s choice to engage in challenging listening tasks. Previous studies have interpreted physiological responses in conjunction with behavioral responses as markers of task engagement. The aim of the current study was to investigate the effect of potential changes in physiological arousal, indexed by the pupil baseline, on task engagement over the course of an auditory recall test. Furthermore, the aim was to investigate whether working memory (WM) capacity and the signal-to-noise ratio (SNR) at which the test was conducted had an effect on changes in arousal. Twenty-one adult hearing aid users with mild to moderately severe symmetrical sensorineural hearing loss were included. The pupil baseline was measured during the Sentence-final Word Identification and Recall (SWIR) test, which was administered in a background noise composed of sixteen talkers. The Reading Span (RS) test was used as a measure of WM capacity. The findings showed that the pupil baseline decreased over the course of the SWIR test. However, recall performance remained stable, indicating that the participants maintained the necessary engagement level required to perform the task. These findings were interpreted as a decline in arousal as a result of task habituation. There was no effect of WM capacity or individual SNR level on the change in pupil baseline over time. A significant interaction was found between WM capacity and SNR level on the overall mean pupil baseline. Individuals with higher WM capacity exhibited an overall larger mean pupil baseline at low SNR levels compared to individuals with poorer WM capacity. This may be related to the ability of individuals with higher WM capacity to perform better than individual with poorer WM capacity in challenging listening conditions.